Grigorij Tyeplov, a 18. századi polihisztor - Pásztor Renáta (Acta Universitatis Szegediensis : acta historica, 2021)
The topic of this study is the presentation of the life and work of the 18th-century Russian polyhistor and statesman Grigorii Nikolaevich Teplov. Teplov was very diversified in the second half of the 1700s. As a statesman, his influence in the court was significant during the reign of Catherine II, among other positions, he held the position of senator, and his cultural and scientific legacy is significant, as he worked as a painter, a musician, and even some of his philosophical works survived. In my study, I want to focus primarily on Grigorii Teplov’s political career, his position in the court, and his relationship with the territories of Little Russia.